Association of Some Hormones with Anthropometric Measurements in Women - Mohammad, Fatima A.; Abdulkareem, Nadia Ghassan (Iraqi Journal of Science, 2025)
Hormones play a vital role in regulating physiological processes throughout the human body. These chemical messengers are synthesized and secreted by specialized glands and organs known as endocrine tissues. The aim of the study is to investigate the linkage among different serum hormones including: estradiol, insulin, kisspeptin, leptin, leptin receptor (R), and testosterone with anthropometric measurements like age, body mass index (BMI), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and waist to hip ratio (WHR) in women to find a new mechanism for early detection of various diseases. A cross-sectional comparative study was conducted to examine various health indicators among 150 healthy Iraqi women between the ages of 19 to 49 years. They were divided into three groups, each involving 50 women, according to their weight and BMI: control, overweight, and obese. Venous blood samples withdrawn from all subscribers to obtain serum, which was then analyzed using enzyme-linked immunosorbent assay (ELISA) to measure levels of hormones. A highly significant elevation of WHR was found in obese women compared to overweight and control women. Also, there was a significant rise in HOMA-IR and hormones such as insulin, kisspeptin, leptin, and its receptor in obese women in comparison to the control group. Obese and overweight women exhibited a notable reduction in estradiol levels, while testosterone levels showed a significant decline exclusively in obese women. Obese women exhibited highly significant negative association among estradiol and testosterone with anthropometric measurements, whereas strong significant positive correlations discovered among anthropometric measurements with hormones, leptin-R and kisspeptin. The study's findings of significant differences in hormone levels associated with elevated anthropometric measurements, particularly in obese women, suggest these hormonal imbalances may contribute to the development of certain diseases.